Role of Emotional Intelligence in Leadership and Organizational Performance in Indonesia - Amisha, Budiwati (International Journal of Psychology, 2024)
Purpose: The aim of the study was to investigate the role of emotional intelligence in leadership and organizational performance. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Emotional intelligence plays a crucial role in leadership and organizational performance by enhancing leaders' abilities to understand and manage their own emotions and those of others. Leaders with high emotional intelligence are better equipped to navigate complex interpersonal dynamics, inspire trust, and foster positive workplace cultures. Consequently, organizations led by emotionally intelligent leaders often experience higher employee engagement, productivity, and overall performance. Unique Contribution to Theory, Practice and Policy: Trait theory of leadership, transformational leadership theory & social exchange theory of creativity may be used to anchor future studies on the role of emotional intelligence in leadership and organizational performance. Develop customized leadership training programs that focus on enhancing emotional intelligence competencies such as self-awareness, self-regulation, empathy, and social skills. Advocate for the integration of emotional intelligence training into formal leadership development programs at organizational and institutional levels.